PENGARUH PEMBERIAN PUPUK KOMPOS BERBAHAN DASAR AMPAS SAGU TERHADAP PERTUMBUHAN VEGETATIF TANAMAN JAGUNG (Zea mays L) - Fitrianti Maninggir; Verry R. Ch. Warouw; Meldi T. M. Sinolungan (Universitas Sam Ratulangi, 2018)
ABSTRACT This research aimed to know the effect of the given compost-based sago fibres to the vegetative growth of corn. Taking the dregs of sago in the village of Salurang, subdistrict of South Central Tabukan, regency of Sangihe Islands. This was carried out in the Faculty of Agriculture University of Sam Ratulangi Manado. The soil and the dregs of sago were analized at Laboratory of Chemistry and Soil Fertility, Faculty of Agriculture University of Sam Ratulangi Manado. This study used a Random Completed Design (RCD), which consisted of ten treatment combinations and repeated as much as 3 times, so that the retrieved 30 pot experiments. Each pot contained a soil experiment weighing of 5 kg. The research results showed that every treatment there was significant effects of height corn plants, the amount of corn leaves, wet weight of header section, wet weight of plant root and dry weight of header section, however no significant effect to the dry weight of root section of corn plants. The best combination of mixed soil with compost-based sago fibres was a combination of soil and compost based sago fibres on a dose of 30 tons/ha. Keywords: plant corn (Zea mays L), sago fibres compost